2023
DOI: 10.26434/chemrxiv-2023-6mg3w-v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carboxylate catalysis: a mild catalytic O-silylative aldol reaction of aldehydes and ethyl diazoacetate

Abstract: A mild catalytic variant of the aldol reaction between ethyl diazoacetate and aldehydes is described using a combination of N,O-bis(trimethylsilyl)acetamide and catalytic tetramethylammonium pivalate as catalyst. The reaction proceeds rapidly at ambient temperature to afford the O-silylated aldol products in good to excellent yield, and the acetamide byproducts can be removed by simple filtration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…8,9 Catalytic deprotonation reactions of alkynes without metals are presumed to be highly challenging, 10 although reactions with aldehydes and ketones (Favorskii reaction) have been realized with strong metal-free bases such as quaternary ammonium hydroxides. 11−13 We have previously shown that metal-free catalytic enoyl isomerization 14 and silylative aldol reactions 15 are possible with simple carboxylate salt catalysts, without the need of metal or strong (and potentially nucleophilic) hydroxide bases. In the aldol reaction, the combination of tetramethylammonium pivalate (TMAP) and the neutral silylating agent N,Obis(trimethylsilyl)acetamide (BSA) was required for rapid turnover rates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Catalytic deprotonation reactions of alkynes without metals are presumed to be highly challenging, 10 although reactions with aldehydes and ketones (Favorskii reaction) have been realized with strong metal-free bases such as quaternary ammonium hydroxides. 11−13 We have previously shown that metal-free catalytic enoyl isomerization 14 and silylative aldol reactions 15 are possible with simple carboxylate salt catalysts, without the need of metal or strong (and potentially nucleophilic) hydroxide bases. In the aldol reaction, the combination of tetramethylammonium pivalate (TMAP) and the neutral silylating agent N,Obis(trimethylsilyl)acetamide (BSA) was required for rapid turnover rates.…”
mentioning
confidence: 99%
“…Since control experiments without the TMAP catalyst (Table 1, entry 7) or with the alternative CF 3 -substituted silylating agent BSTFA (Table 1, entry 6) resulted in no reaction, the catalytic cycle appears to require both species. We propose a probase mechanism involving an initial silyl transfer from BSA to the pivalate anion of TMAP, 15 leading to formation of anionic species I (Scheme 4) 37−40 with subsequent deprotonation of the alkyne (Scheme 4). This mechanism is supported by the inertness of BSTFA, which should give rise to a weaker base.…”
mentioning
confidence: 99%